TINJAUAN HUKUM TERHADAP PEMBERIAN PENGHASILAN TETAP DAN TUNJANGAN PERANGKAT DESA DALAM MENUNJANG PENYELENGGARAN PEMERINTAHAN DESA (Studi Di Desa Purwo Agung Kecamatan Masama Kabupaten Banggai) - AMIN AMIN; FIRMANSYAH FALITY (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2019)
This research aims to know the implementation of the grant of a steady income and benefits of the device support the holding of village governance at the village Purwoagung village sub district of Banggai Regency Masama, as well as to find out the factors that affect the implementation of the grant of a steady income and benefits of the device support the holding of village governance at the village Purwoagung village sub district of Banggai Regency Masama. Based on research and discussion of the obtained results that Implementation of the grant of a steady income and benefits of the device support the conduct of the Government of the village village in the village of Great Purwo Subdistrict Masama Banggai Regency has been implemented. In determining the quantities fixed and living allowances are based on the regulations of the Banggai Regent Number 2 Year 2018 On the procedures for the determination of the magnitude of a steady income and benefits For the village chief and the device as well as Deliberative Body Perks Village village (BPD) in Banggai Regency and Banggai Regent Decree Number 141/259/DPMD About The determination of the magnitude of a steady income and benefits the village chief and the Village as well as the Consultative Body of the village Perks (BPD) each village se-Banggai Regency 2018 fiscal year. As for the factors that influence the implementation of the grant of a steady income and benefits of the device support the conduct of the Government of the village village in the village of Great Purwo Subdistrict Masama Banggai Regency, there are factors that affect the . Where those factors include legal factors is supporting factors and the availability of budget. While restricting factor is the delay in the construction of Administration